RADEC (Read-Answer-Discuss-Explain And Create) as a New Learning Model in Indonesia: How Does it Impact on the Science Literacy of Primary School Students? - Salma Ihsani Fhilrizki; Wahyu Sopandi; Mimin Nurjhani Kusumastuti; Irfan Fauzi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The article aimed to investigate in detail the impact of the RADEC (Read-Answer-Discuss-Explain And Create) learning model on primary school students' science literacy in the water cycle material. This study used a quantitative approach with a pre-experimental design. This research was conducted on 100 primary school students in Bandung, Indonesia. The data collection technique was using observation and science literacy tests. Observations were used to see the implementation of the RADEC learning model, and tests were used to see the impact of the RADEC learning model on students' science literacy. The results of this study indicated that the RADEC learning model on the water cycle material can be implemented well. In addition, the RADEC learning model has proven to have an impact on students' science literacy, this could be seen from the results of the N-Gain score of science literacy, which was 0.48 in the medium category. The results of the mean difference test show that there was a significant difference between the pretest and the posttest score, the sig. value of the mean difference test results was 0.000. So, the RADEC learning model had an impact on students' science literacy in primary schools. This research contributed to education in an effort to realize meaningful learning through the implementation of an innovative learning model, namely the RADEC learning model, and this model was very suitable to be applied in learning to develop various skills in the 21st century, including science literacy